The starfish and the Spirit : unleashing the leadership potential of churches and organizations - Ford, Lance, 1964-; Wegner, Rob, 1970-; Hirsch, Alan, 1959 October 24- (Grand Rapids Zondervan, 2021)
"The Starfish and the Spirit is about creating a culture where church leaders view themselves as curators of a community on mission, not the source of certainty for every question and project. It is about creating a team of humble leaders "in the middle" of the church, not at the top--leaders who naturally reproduce multiple generations of leaders, from the middle out on mission. Imagine a church led by a team whose gifts and talents are completely unleashed, enabling everyone to show up and step up with all they really are. The joy and vigor coming from the collective strength, intelligence, and skill in the community of leaders not only brings greater potency but better yields for your ministry as well. What would it be like to see this kind of healthy leadership reproduced into the second, third, and fourth generation, on multiple strands?"--
Keywords: Christian leadership; Mission of the church; Leadership -- Religious aspects -- Christianity